Does in utero exposure of antiepileptic drugs lead to failure to reach full cognitive potential?. (May 2015) - McCorry, D.; Bromley, R.
Highlights: Valproate harm is dose related. Lower than 1000 mg of VPA is not significant different to other standard AEDs. Little data pertaining to levetiracetam exposure and other new AEDs is available. More evidence is required for high dose lamotrigine and polytherapy. Abstract: A clinical scenario of a young female on 800 mg of sodium valproate (VPA) who has recently failed lamotrigine (LTG) and levetiracetam (LEV) and who is currently planning a pregnancy is presented. Currently available data pertaining to the longer-term development of children exposed to antiepileptic drugs (AEDs) are reviewed along with considerations around the methodology and interpretation of such research. There is an accumulation of data highlighting significant risks associated with prenatal exposed to VPA, with the level of risk being mediated by dose. The majority of published evidence does not find a significant risk associated with carbamazepine (CBZ) exposure in utero for global cognitive abilities however the evidence for more specific cognitive skills are unclear. Limited data indicate that LTG may be a preferred treatment to VPA in terms of foetal outcome but further evidence is required. Too little data pertaining to LEV exposure is available and a lack of evidence regarding risk of this and other new AEDs should not be interpreted as evidence of safety.